OPTIMASI PENGELOLAAN KEUANGAN DALAM RANGKA MENINGKATKAN KINERJA KEUANGAN DI PEMERINTAH DAERAH KABUPATEN BOGOR - Timbul; Parulian Hutagaol; Ma'mun Sarma (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2025)
ABSTRACT Alongside the perceived complexity of state financial management by some members of society, the management of state finances fundamentally aligns with the goal of achieving good governance. There are four fundamental principles of state financial management based on good governance: (1) accountability in financial management based on results or performance; (2) transparency in every government transaction; (3) empowerment of professional managers; and (4) the presence of a strong, professional, and independent external audit institution, avoiding duplication in audit implementation. This study aims to formulate optimization strategies for regional financial management to enhance the financial performance of the region in Bogor Regency using SWOT analysis. The analysis resulted in four strategies, namely strengthening local government policy regulations on financial governance to facilitate implementation and enhance the effectiveness of financial governance in accordance with regulations; increasing the government's commitment to the development of human resources and competencies of financial management officials; improving the quality of information systems and technology to strengthen the database and accuracy of local financial management; and enhancing monitoring and evaluation of financial management. Keywords: effectiveness, finance, strategy, SWOT